2009
DOI: 10.1089/dia.2008.0041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accuracy, Reliability, and Clinical Applicability of Continuous Glucose Monitoring (CGM): Is CGM Ready for Real Time?

Abstract: CGM detects abnormalities in glycemic control in a manner heretofore impossible to obtain. However, our studies revealed sufficient incongruence between simultaneous laboratory blood glucose levels and interstitial fluid glucose (after calibrations) to question the fundamental assumption that interstitial fluid glucose and blood glucose could be made identical by resorting to algorithms based on concurrent blood glucose levels alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 14 publications
2
60
1
Order By: Relevance
“…1 Continuous glucose monitoring is actually recognized as the only technique with the ability to provide complete diurnal/nocturnal glucose patterns and supply trend information. 1,2 Several clinical studies have indicated that utilization of CGM data, both retrospectively and in real time, can help adjust insulin therapies, prevent (or minimize the occurrence of) extreme glycemic excursions, 3,4 reduce glycated hemoglobin values, 5,6,7 and achieve a tight glycemic control in both intensive care 8,9 and surgical units. 10 Despite these clear advantages, utilization of CGM techniques is still limited in the current clinical practice, mainly because of concerns about their accuracy, reliability, robustness, and patient tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…1 Continuous glucose monitoring is actually recognized as the only technique with the ability to provide complete diurnal/nocturnal glucose patterns and supply trend information. 1,2 Several clinical studies have indicated that utilization of CGM data, both retrospectively and in real time, can help adjust insulin therapies, prevent (or minimize the occurrence of) extreme glycemic excursions, 3,4 reduce glycated hemoglobin values, 5,6,7 and achieve a tight glycemic control in both intensive care 8,9 and surgical units. 10 Despite these clear advantages, utilization of CGM techniques is still limited in the current clinical practice, mainly because of concerns about their accuracy, reliability, robustness, and patient tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these agents, when used in combination with basal insulin and metformin, can flatten the postprandial glucose profile without increasing the risks of hypoglycemia and weight gain often associated with prandial insulin treatment (26)(27)(28)(29). In addition, improved devices for continuous glucose monitoring (CGM) allow for more complete assessment of 24-h glycemic patterns (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…So why do patients, who are otherwise accustomed to wearing chronically semi-invasive devices, not want to use CGM on a regular basis? Apart from some general reasons such as discomfort, high cost, and low reliability, 8 the main cause is probably related to the primary reason for undergoing CGM, which is to allow patients to make better decisions. This aim, however, is something that seems to have been forgotten by manufacturers.…”
Section: Clinical Evidence On Efficacy and Reasons For Continuous Glumentioning
confidence: 99%